Pengaruh Penerapan Model Pembelajaran Kooperatif Teknik Keliling Kelompok Terhadap Pemahaman Konsep Matematis Kelas VIII SMPN 14 PadangTahun Pelajaran 2012/2013, Skripsi, Program Studi Pendidikan Matematika, STKIP PGRI Sumatera Barat, Padang, 2013. - iswadi, Hary; K, Delsi; Yunita, Alfi (Pendidikan Matematika, 2013)
This research was based on the preliminary research on students of Junior High School 14 (SMPN 14) Padang who got low understandingÂ  in mathematics concept.Â  This research was aimed at determining whether studentsâ understanding mathematics concept by applyingÂ  one of cooperative learningÂ  called club round technique was better than applying any other convensional techniques in teaching mathematics at grade VIII of SMPN 14 Padang.This research was experimental research by having random sampling. The population were grade VIII students of SMPN 14 Padang. In order to get the sample, the researcher used random sampling and it was chosen that grade VIII. 6 students were as the experiment class and grade VIII. 5 students as the control class. The instrument used in this research was achievement test. The test form used was essay with the relialibilityÂ  =0,76. The data analysis technique used was the t-test of the party at Î± =0,05 with the use of Minitab Software.Â  Based on the analysis from those two classes, it were normally distributed and homogenous at the significance level Î± = 0,05 and the results obtained from testing the hypothesis P-value = 0,039, so the hypothesis was accepted. Therefore, it could be conluded that the studentsâ understanding of the mathematics concept by implementing cooperative learning, club round,Â  was better than implementing the conventional learning technique at grade VIII of SMPN 14 Padang.